2014
DOI: 10.1111/avsc.12151
|View full text |Cite
|
Sign up to set email alerts
|

Stand management to reduce fire risk promotes understorey plant diversity and biomass in a semi‐aridPinus halepensisplantation

Abstract: Questions: How do thinning and understorey management practices (ploughing, clearing) to reduce fire risk affect plant species composition, diversity and biomass within pine plantations on previous croplands? Do managed pine plantations promote changes in plant succession compared to unplanted areas (old fields) towards restoration goals including holm oak forest or other alternative land-use types?Location: Altiplano del Conejo, Guadix-Baza Basin, SE Iberian Peninsula, Spain.Methods: We evaluated plant specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Graminoids (Table ) had higher richness values in the BC position, which do not coincide with that found in high density old plantations of the region, where evergreen perennial herb and graminoid richness decreased significantly when compared with the shrubland (Giorgis et al., ). Therefore, our findings agree with those of other authors who have documented differences in biodiversity indicators according to the silvicultural management strategies applied in the plantations (Brockway & Outcalt, ; Greene et al., ; Jiménez et al., ). Finally, the PCA ordination (Figure ) was consistent with the results obtained by analysing differences between treatments in terms of site conditions and life forms.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Graminoids (Table ) had higher richness values in the BC position, which do not coincide with that found in high density old plantations of the region, where evergreen perennial herb and graminoid richness decreased significantly when compared with the shrubland (Giorgis et al., ). Therefore, our findings agree with those of other authors who have documented differences in biodiversity indicators according to the silvicultural management strategies applied in the plantations (Brockway & Outcalt, ; Greene et al., ; Jiménez et al., ). Finally, the PCA ordination (Figure ) was consistent with the results obtained by analysing differences between treatments in terms of site conditions and life forms.…”
Section: Discussionsupporting
confidence: 93%
“…light, soil water and nutrients), soil acidification or litter accumulation, which inhibit the establishment of the understorey species (Amiotti, Zalpa, Sánchez, & Peinemann, ; Cortés, Chamorro, & Vega, ; Gómez‐Aparicio, Zavala, Bonet, & Zamora, ; Michelsen, Lisanework, Friis, & Holst, ). In contrast, other authors consider that plantations may contribute to an increase of biological diversity when they are established in degraded ecosystems, without replacing natural forests (Jiménez, Spotswood, Cañadas, & Navarro, ). This increase in species diversity may be explained by the creation of low‐light microhabitats suitable for colonization by shade‐tolerant species in otherwise high‐light environments (Belsky, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neeson et al (2015) suggested coordination among initiatives on both temporal and spatial scales to optimize the use of resources and the outcome of one-time restoration events. Others have returned to restored sites before they have fully recovered and made further adjustments based on new knowledge of the design and outcomes of monitoring (Harms and Hiebert 2006, van Dijk et al 2007, Jim enez et al 2015, Nilsson et al 2017. Our results are an example of the efficacy of the latter approach.…”
Section: Discussionmentioning
confidence: 76%
“…Aquatic passive and aerial passive refer to taxa that are aquatic or aerial passive dispersers, respectively. Others have returned to restored sites before they have fully recovered and made further adjustments based on new knowledge of the design and outcomes of monitoring (Harms and Hiebert 2006, van Dijk et al 2007, Jim enez et al 2015, Nilsson et al 2017. failures (where not only ecological but even basic geomorphological goals are not met) but, in most cases, fall somewhere in between (Suding 2011).…”
Section: Discussionmentioning
confidence: 99%